Library and Town Hall, Port of Spain - (:unkn) unknown (My University, 2010)
This vintage photo features a building in Knox Street, Port of Spain, Trinidad which houses the Public Library and Town Hall. Part of the building is fenced and it is surrounded by trees.
Colour: Black and White ; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; City halls--Trinidad and Tobago; Library buildings--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Library architecture--Trinidad and Tobago